Hepatic steatosis and development of type 2 diabetes: Impact of chronic hepatitis B and viral specific factors - Ming-Whei Yu; Chih-Lin Lin; Chun-Jen Liu; Yi-Wen Huang; Jui-Ting Hu; Wan-Jung Wu; Chih-Feng Wu (Journal of the Formosan Medical Association, 2022)
Background: Chronic hepatitis B (CHB) was associated with a lower prevalence of nonalcoholic fatty liver disease (NAFLD). The impact of CHB on the link between NAFLD and type 2 diabetes (T2D) and related virological implications remain unclear. Methods: We recruited 2255 middle–to older–aged individuals who were examined serially for hepatic steatosis by ultrasonography and blood biochemistry as part of a population-based hepatocellular-carcinoma cohort study. In CHB patients, hepatitis B surface antigen (HBsAg) seroclearance and variation in viral load trajectory were also evaluated. Results: During the average follow-up of 6 years, 168 participants developed T2D. CHB, as compared with uninfected subjects, was associated with lower risks for both new development and persistence of hepatic steatosis. Furthermore, the risk of steatosis decreased with higher levels of past viral load trajectories (p for trend = 0.0002). However, concomitant steatosis at baseline in CHB patients was still significantly associated with a 1.98-fold increased risk for T2D after multivariate adjustment including age, impaired fasting glucose, cirrhosis, and time-varying body mass index, although CHB reduced the propensity of hepatic steatosis to develop diabetes, especially for patients with high levels of past viral-load trajectory. In CHB, the functional cure of HBV infection, as indicated by HBsAg seroclearance, was associated with a 1.41-fold (95% CI 1.12–1.79) increased risk of steatosis. In addition, the increased risk for progressive impairment of glucose metabolism due to steatosis was especially prominent after HBsAg seroclearance. Conclusion: The data showed that HBV interferes with fatty liver disease and modulates its related T2D risk, offering additional insight into the interplay between NAFLD and CHB.